The Impact of the Strategic Supplier Partnership, and Strategic Outsourcing on the Supply Chain Performance: The Mediating Role of Customer Relationship - Chairit Thongrawd; Chakrit Skulitsariyaporn; Somchawee Sirisopana; Narumon Chomchom (International Journal of Supply Chain Management, 2020)
Abstract- The main focus of the current study is to examine the impact of the strategic supplier partnership, and strategic outsourcing on the supply chain performance. Additionally, the study has mediating role of the customer relationship in the relationship between the strategic supplier partnership and the organizational performance and in the relationship between the strategic outsourcing and the organizational performance. The study is carried out on the manufacturing firms in the Indonesia. The final sample comprises of the 310 questionnaire and the response rate is turned out to be 65.12 percent. In order to examine effects within the construct and to carry out hypotheses testing, this study employed Partial Least Square (PLS) path modeling, has developed PLS, as a procedure to determine path model involving indirectly measured latent constructs by a set of indicators. It is suitable to apply PLS when there is large number of exogenous latent constructs to estimate a few endogenous constructs. The findings of the current study, view supply chain management as a strategic and operational tool to integrate business operations in building capabilities for customization which promises a sustainable customer satisfaction by effectively manages the total flow of inventory from ultimate supplier to the end user The findings of the study would also be useful in identifying and developing assistance and consultancy programs needed by automobile firms, especially those that are important for improving their skills and knowledge that they need for competing in the marketplace.